PENINGKATAN KINERJA GURU PPKN MELALUI PELATIHAN DAN PENGEMBANGAN PROFESIONAL UNTUK OPTIMALISASI HASIL BELAJAR SISWA - Nurfalah Nurfalah; Muhammad Nabil Asauri; Albar Alhaetami; Awal Ramadhan; Irfan Panji Gumelar; Nadila Maharani (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2025)
Teacher performance is one of the key factors influencing the quality of both the learning process and student outcomes, including in the subject of Civic Education (PPKN). However, various challenges such as limited innovation in teaching methods and a lack of professional development still hinder the achievement of optimal learning goals. This study aims to analyze the improvement of Civic Education teachers’ performance through training and professional development programs and their impact on optimizing student learning outcomes. The research employed a qualitative approach with data collection techniques including interviews, observations, and documentation involving teachers and students from several schools. The findings indicate that continuous training and well-structured professional development enhance teachers’ pedagogical and professional competencies, as reflected in more comprehensive lesson planning, varied teaching methods, and assessments aligned with students’ needs. The improvement in teacher performance positively affects students’ learning outcomes, particularly in understanding Civic Education concepts as well as fostering civic attitudes and skills. The implications of this study highlight the importance of ongoing support from schools and the government in organizing structured training and professional development programs, along with regular evaluations to ensure the effectiveness of the learning process.